Corporate innovation and environmental investment: The moderating role of institutional environment - Tian, Jin-Fang; Pan, Chao; Xue, Rui; Yang, Xiao-Tong; Wang, Chen; Ji, Xu-Zhao; Shan, Yu-Li (Advances in climate change research, 2020)
Corporate environmental investment helps improve corporate environmental performance, which, therefore, is an effective micro-level solution to mitigate environmental concerns generated by corporate excessive resource exploitation and energy use. Using Chinese listed firms within environment-related industries over the period 2011–2018 as the research setting, this study applies the panel data model to investigate the impact of corporate innovation on environmental investment, as well as the moderating effects of institutional factors. The results show that corporate innovation significantly improves firms' environmental investment with 1% Research & Development (R&D) investment ratio increase generating 2326 CNY (around 351 USD at 2018 exchange rate) increase in environmental investment; the moderating effect of environment policy is positive and significant while the moderating effect of internationalisation level is not significant, indicating that current environment policy implementation helps to strengthen the positive impact of corporate innovation on environmental investment while the role of internationalisation level in this nexus is not observed. From a micro-level perspective, the findings of this study shed light on mitigating environmental concerns through enhancing corporate innovation, and provide evidence that China's corporate internationalisation process awaits more regulatory controls.